2013
DOI: 10.1021/jf303926v
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Sodium Phytate on the Structural Stability and Solubility of Proteins

Abstract: The interaction between sodium phytate and three proteins was studied using solubility experiments and differential scanning calorimetry (DSC) to assess structural stability. Lysozyme, which is positively charged at neutral pH, bound phytate by an electrostatic interaction. There was evidence that phytate cross-linked lysozyme molecules forcing them out of solution. Myoglobin and human serum albumin, which were neutral or negatively charged, respectively, displayed association rather than binding, and there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 30 publications
0
43
0
1
Order By: Relevance
“…In contrast, when supplemented with additional dietary sources of protein and inorganic P (Method 2), only 18.8% of the phytate P was utilised. The inherent ability of phytate-bound P to chelate proteins via formation of binary protein-phytate complexes below the isoelectric point of the protein is known (Mothes et al, 1990) and this ability is influenced by the type of protein, pH and dietary salts (Yu et al, 2012;Bye et al, 2013). The relatively low phytate-P utilisation observed in birds fed maize-based diets in Method 2 may be attributed, at least in part, to the formation of protein-phytate complexes.…”
Section: Non-phytate P Vs True Digestible Pmentioning
confidence: 99%
“…In contrast, when supplemented with additional dietary sources of protein and inorganic P (Method 2), only 18.8% of the phytate P was utilised. The inherent ability of phytate-bound P to chelate proteins via formation of binary protein-phytate complexes below the isoelectric point of the protein is known (Mothes et al, 1990) and this ability is influenced by the type of protein, pH and dietary salts (Yu et al, 2012;Bye et al, 2013). The relatively low phytate-P utilisation observed in birds fed maize-based diets in Method 2 may be attributed, at least in part, to the formation of protein-phytate complexes.…”
Section: Non-phytate P Vs True Digestible Pmentioning
confidence: 99%
“…Upon ingestion of phytate and passage into the duodenum there is increased secretion of mucin, increasing the presence of endogenous amino acids in the lumen ). Dietary Na has been shown to play a role in the antinutrient effect of phytate and although the mechanism remains unclear, it has been demonstrated that cation/anion balance can disrupt phytate : protein complexes (Liu et al, 2008;Ravindran et al, 2008;Bye et al, 2013). This has been associated with dampening the antagonistic effect of phytate on endogenous amino acid flow .…”
Section: Tablementioning
confidence: 99%
“…However, PAF only has a single sclx 8 binding site (Figure ) and the binding thermodynamics were described adequately by the bidentate ligand model. In an extreme case, a bell‐shaped precipitation response has been observed for lysozyme and phytate, another polycationic protein‐polyanionic ligand system . Precipitation was observed at ∼4 mM phytate, while lysozyme remained soluble at 30 mM phytate.…”
Section: Introductionmentioning
confidence: 99%